Use and mention with respect to ``know”, “believe”, “evidence”, “justification”, “hypothesis”, and so on: A hot mess - Jody Azzouni (Baltic International Yearbook of Cognition, Logic and Communication, 2025)
Use/mention errors are everywhere in epistemology. They even show up in Gettier’s classic paper. They bedevil philosophical attempts to understand “know”, “belief”, as well as propositional-attitude expressions at the most basic level. What, for example, are propositional-attitudes attitudes towards? Not towards propositions, as it turns out. Use/mention errors confuse philosophers in the most simple of ways: For example, they allow philosophers to think that evidence and knowledge are propositional, in the sense that evidence is true propositions and that knowledge is knowledge of propositions. Similarly, propositional attitudes are seen as attitudes towards propositions rather than what propositions describe. It is shown specifically in detail how Williamson’s influential views about E=K—that evidence is what one knows is flawed because of use/mention errors.
Keywords: E = K; “evidence”; existence; facts; “justification”; nouns; propositional-attitude clauses; relative clauses; that-clauses; use/mention errors